Robust PID Performance for Temperature Regulation of Herb Drying System - Mohd Syukri, Muhammad Afif Hakimie; Hamdan, Rohaiza; A. Jalil, Mohd Hafiz (Evolution in Electrical and Electronic Engineering, 2023)
Temperature regulation is important in every aspect of the system process. Many industrial designs also depend on the heating process which requires an efficient temperature regulation system. Hence, to overcome such problems, implementing a system controller that can automatically be tuning, regulate and monitor the temperature of the heating process is proposed. Robust proportional integral derivative (PID) can be used for temperature regulation of herb drying as a system. This paper develops and analyzes the PID controller with robust performance to obtain a robust controller for regulating the process control of the heating element. Based on the comparative studies, the PID controller with the robust performance of the Td Anti-windup scheme produces better performance in terms of rise time, overshoot percentage, and settling time as compared with the normal PID controller as the result of the lowest overshoot percentage of 8.152% in normal condition and 2.577% in load disturbance and set point changes conditions. Next, the settling time is fastest than other controllers to reach the steady state condition with 657.157s in normal conditions and 595.219s in load disturbance and set point changes conditions. Also, the rise time with 173.808s in normal conditions and 272.731s in load disturbance and set point changes condition.